"They Destroy the Reproductive System": Exploring the Belief that Modern Contraceptive Use Causes Infertility. Issue 4 (9th November 2018) - Sedlander, Erica; Bingenheimer, Jeffrey B.; Thiongo, Mary; Gichangi, Peter; Rimal, Rajiv N.; Edberg, Mark; Munar, Wolfgang
Abstract: A common reason for nonuse of modern contraceptives is concern about side effects and health complications. This article provides a detailed characterization of the belief that modern contraceptives cause infertility, and an examination of how this belief arises and spreads, and why it is so salient. We conducted focus group discussions and key informant interviews in three rural communities along Kenya's eastern coast, and identified the following themes: (1) the belief that using modern contraception at a young age or before childbirth can make women infertile is widespread; (2) according to this belief, the most commonly used methods in the community were linked to infertility; (3) when women observe other women who cannot get pregnant after using modern contraceptives, they attribute the infertility to the use of contraception; (4) within the communities, the primary goal of marriage is childbirth and thus community approval is rigidly tied to childbearing; and, therefore (5) the social consequences of infertility are devastating. These findings may help inform the design of programs to address this belief and reduce unmet need.